The Effect of Using Acidified Imperata cylindrica as a Co-substrate with Dairy Cow Manure on the Digesters Performance - Mustikasari, A. R.; Sutaryo, S.; Ufidiyati, N.; Purnomoadi, A. (Tropical Animal Science Journal, 2023)
The objective of the current study was to examine the effect of the utilization of acidified cogon grass (CG) (Imperata cylindrica) as a co-substrate for the anaerobic digestion of dairy cow manure (DCM). Four continuous stirred-tank reactor (CSTR) digesters with various substrate compositions, namely, T1 (100% DCM), T2 (95% DCM and 5% CG), T3 (95% DCM and 5% acidified CG using 4% H2SO4 solution), and T4 (95% DCM and 5% acidified CG using Wuluh star fruit (Averrhoa bilimbi L) filtrate), were operated. This study was conducted for 66 d or 3 hydraulic retention times (HRTs). Also, it evaluated the methane production of the digested slurry of each CSTR digester (batch-type) with five replications in each treatment. The results indicated that the methane production in T2, T3, and T4 in the unit of L/kg substrate increased by 35.52%, 41.95%, and 45.44%, respectively, compared with that in T1. Furthermore, the productions in T3 and T4 increased by 4.35% and 7.25%, respectively, compared with that in T2. The production from the slurries of CSTR digesters in units of L/kg substrate and L/kg volatile solid (VS) showed significantly different results (p0.05). Therefore, with or without acidification, CG can be used as a co-substrate with DCM to enhance methane production.